The Influence of External Environment, Internal Environment and Management Competence on The Quality of Company Strategies in Kulonprogo Regency, Yogyakarta - Sumiyanto, Ahmad (Journal of Economics, Business, Accounting and Management, 2025)
This study aims to analyze the influence of external environmental analysis, internal environmental analysis, and management competency on the quality of the resulting strategy. This study is expected to help provide insight for company leaders or managers about the importance of strategy quality in improving company performance. The population in this study was all medium and large companies/industries registered with the Kulonprogo Regency Industry and Trade Office, totaling 88 companies. To obtain a suitable sample in this study, the non-random sampling technique used in this study was Purposive Sampling Technique. The quantitative analysis used in this study was multiple linear regression analysis with the help of the SPSS program. Based on the research results and discussion above, it can be concluded that the higher the intensity of external environmental analysis, internal environment analysis, and management competency, the higher the quality of the resulting strategy.